Revisiting The Handmaid's Tale: reading the novel through a scientific lens - Wan Yahya, Wan Roselezam; Chin, Koon Poh (Contemporary Research Center, 2013)
Atwood’s novel The Handmaid’s Tale (1985) has enabled us to see how science can be used to interpret, analyze and relate to the various aspects highlighted in it. Prompted by the seminal reading of this text by June Deery (1997), this article revisits the scientific approach relating to physics to explore different elements in the novel. The representation of time and its relation to space and matter is explored in a manner that casts new light on the understanding of: how time could actually affect characters’ past, present and future; how the effects of the space-time relation could affect one’s energy by relating it to the characters’ disorientated state of mind; how science makes a connection between nature and male dominance, and the portrayal of women and men based on Newtonian mechanics and quantum physics. From this novel, much can be analyzed and explored using science as an instrument, thus offering many possibilities and a different perspective to readers consider and which revolve around the issue of how men and women are viewed.